Vortex suppression on high subsonic turbine blade via micro holes (30 Degree) / Mohd Hafiz Mohd Noh, Ahmad Hussein Abdul Hamid, and Koichi Moris - Mohd Noh, Mohd Hafiz; Abdul Hamid, Ahmad Hussein; Moris, Koichi (Universiti Teknologi MARA, 2022)
The vortex shedding of a turbine blade is suppressed by making a hole, connecting between the pressure side and suction side in the area of the trailing edge. Computational simulation has been done via numerical code by using Spalart–Allmaras turbulence model with Delayed Detached Eddy Simulation. The exit Reynolds number is 2.8 × 106 and the exit isentropic Mach number is 0.79. The size of the hole is 0.094D with a connecting angle of 30 degrees. The result shows that the vortex has successfully been suppressed at the turbine trailing edge and turbine wake area. The micro-hole is capable to reduce initial vortex formation which can be confirmed by the decrement of frequency peak and via observation of flow field vortex simulation.